ANARCHISM OF FOOTBALL SUPPORTERS IN THE PERSPECTIVE OF SPORTS SOCIOLOGY - Selvi Yoslanda; Phil Yanuar Kiram; padli padli; Fiky Zarya (MAJORA: Majalah Ilmiah Olahraga, 2022)
The purpose of writing this article is to examine the anarchism of football supporters from the aspect of sports sociology. The search for this article uses a qualitative descriptive method through literature studies sourced from references that are willing to be studied conceptually and inferred from the results of the discussion. The results of this study found that the factors causing anarchism in football supporters from the aspect of sports sociology include: 1) media exposure can increase high aggression and anger after watching a game. 2) because the referee's leadership in the match is not fair to stimulate polemics in the viewers, 3) Disappointment with the quality of the games displayed, and 4) there is a sense of love and fanaticism in the supporters that causes it to play a role beyond rationality. This research is expected to be a knowledge and consideration for football supporters so that it can minimize the formation of conflicts and anarchism actions both on and off the field so that conducive sports are formed which will increase sports achievements.